ANALISIS PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA DENGAN MOTIVASI KERJA SEBAGAI MODERASI (Survei Pada Karyawan Banaran9 Coffee and Tea Colomadu) - Inten Fathonah Soegeng, Sutarno & Lamidi (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2018)
This study aims to analyze the significance of influence of leadership style andwork environment on employee performance with work motivation as moderationvariable. The survey was conducted on Banaran9 Coffee and Tea Colomadu employees.Types of data use qualitative data and quantitative data. Data sources use primary datasources and secondary data. The research population is employee of Banaran9 Coffeeand Tea Colomadu with sample of 33 respondents using census technique. Datacollection techniques used questionnaires and observations. Data analysis techniquesuse instrument test, classical assumption test, multiple linear regression, t test, F testand coefficient of determination and test the value of absolute difference. The resultsshowed that leadership style has a positive and significant effect on employeeperformance. The work environment is negatively affiliated with employee performance.Motivation of work has a significant and positive impact on employee performance.Motivation does not moderate the leadership style and work environment onperformance.Keywords: Leadership style, work environment, work motivation, employeeperformance.